Fascicular Visual Field Defects in Open-Angle Glaucoma: Evaluation with Microperimetry - Loredana Arrico; Rossella Giannotti; Manuela Fratipietro; Romualdo Malagola (Journal of Ophthalmology)
Purpose. Use of microperimetry (Mp-1), correlating with Humphrey perimetry (30-2 program), in patients affected by primary open-angle glaucoma (POAG) with perimetric defects, in order to obtain an evaluation of the accuracy of the results obtained by Mp-1. Materials and Methods. In this study 40 eyes of 25 patients affected by POAG with perimetric defects were included. All patients underwent microperimetry test by Nidek Mp-1 (NAVIS software version 1.7.2, Nidek Technologies). Mean sensitivity values expressed in decibel (dB) of all tested dots and mean values for each quadrant obtained by microperimetric test were correlated with corresponding quadrants obtained by static perimetry analysis. Data were analyzed by Pearson’s correlation and Bland-Altman analysis. Results. Interpolated data showed that mean sensitivity values in all spots tested by Mp-1 (11.98 dB, SD 4.31) may be significantly correlated with mean total values obtained by Humphrey 30-2 perimetry (17.95, SD 4.32), with correlation coefficient of 0.556. Conclusions. Topographic visualization of the perimetric alteration by microperimetry allows retesting areas with reduced sensitivity which are topographically visualized and displayable on the ocular fundus examination, avoiding worsening of the functional defect by better modulation of the antiglaucoma therapy and therefore it allows better monitoring of the pathologic functional damage.